State-feedback stabilization for stochastic high-order nonholonomic systems with Markovian switching. (November 2015) - Du, Qinghui; Wang, Chaoli; Wang, Gang; Zhang, Dongkai
Abstract: This paper investigates the problem of stabilization control design for a class of stochastic high-order nonholonomic systems with Markovian switching. A state feedback controller is obtained by using input-state scaling technique and the generalized Itô formula, and adding a power integrator backstepping approach. The switching strategy is proposed to eliminate the phenomenon of uncontrollability and to guarantee that closed-loop system has a unique solution and the solution of the closed-loop systems is almost surely asymptotically stable. Simulation examples demonstrate the effectiveness of the proposed scheme.